Electrode Management ? Investigation Into Soft Breaks At 48MVA FeCr Closed Furnace - C. R. Ray; P. K. Sahoo; S. S. Rao (The Southern African Institute of Mining and Metallurgy, 2007)
Good operation of Soderberg electrodes is dependent upon high quality electrode paste coupled with better electrode management procedures. Without having a good electrode operation, it is not possible to obtain the best outcome from the furnace. In other words that is a good way to say how important the proper electrode operation is. Good electrode performance depends on the slipping rate and current levels, which decides the shape of the baking curve at the level of just below the contact clamps. Negative curvature of baking zone in the central part is considered dangerous because shrinkage takes place outwardly creating abnormal stresses in the electrode. Soft breakages occur when the baking zone comes below the clamps and the casing cannot take the current. This paper deals with various factors affecting baking characteristics leading to soft breakages and also presents case studies in a closed 48MVA furnace with smelting for charge chrome. In case studies in a closed furnace, it has happened that the energy for baking at the low current operation before breakage has been lower than the actual slipping has demanded. At low current there should not be problem, but a problem can occur when the current for some period is raised above the current carrying capacity of the casing. So data for electrode operation in actual period was studied and presented in this paper.